1976
DOI: 10.1002/bit.260180810
|View full text |Cite
|
Sign up to set email alerts
|

Continuous regeneration of NAD(P)+ by flavins covalently bound to sepharose

Abstract: Various flavins, FMN, FAD, and acriflavin, were immobilized to Sepharose using several different coupling methods. The only product stable enough to permit extended studies was acriflavin coupled to epoxy-substituted Sepharose. The nonenzymic oxidizing capacity towards NAD(P) H was investigated and a 25% specific activity, compared to that of free acriflavin, was observed. The reduced acriflavin was immediately auto-reoxidized in air and could thus be reused. It was shown that acriflavin-Sepharose preparations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…These results are superior to others previously described with free or immobilized recycling systems [2,18,19], however, the long-term stability of the enzyme should be improved which could probably be obtained by immobilizing the later on an adequate support.…”
Section: Long-term Stability Of Yeast Alcohol Dehydrogenase/flavopolycontrasting
confidence: 52%
See 1 more Smart Citation
“…These results are superior to others previously described with free or immobilized recycling systems [2,18,19], however, the long-term stability of the enzyme should be improved which could probably be obtained by immobilizing the later on an adequate support.…”
Section: Long-term Stability Of Yeast Alcohol Dehydrogenase/flavopolycontrasting
confidence: 52%
“…In 1976, Mansson et al [2] showed that this latter difficulty can be easily overcome by the immobilization on a particulate support of a chemical oxidant, a flavin derivative, commonly used as a regenerating reagent of 1,4-dihydronicotinamide.…”
Section: Use Of a Polymer-bound Flavin Derivative For The Rapid Regenmentioning
confidence: 99%
“…TTN for NAD have reached 1125. Polymerized FMN (Chambers et al, 1974) and immobilized acriflavin (Mansson et al , 1976) have also been used to regenerate NAD photochemically.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…Alternative procedures include electrochemical regeneration, a method still in its infancy, like the chemical approach utilizing artificial electron acceptors and donors. I n a recent example of the latter method, an electron acceptor, acriflavin, was immobilized on a gel to allow subsequent facile removal from the assay mixture (145). In this form it was used for the continuous nonenzymic oxidation of NADH.…”
Section: A Retention and Regeneration Methodsmentioning
confidence: 99%